Appraisal and Prospects of the Second Five Year Plan - Planning Commission, Government of India (Planning Commission, Government of India, 1958)
A strain on resources, both internal and external, has been felt continuously since the commencement of the Second Five Year Plan. Wholesale prices had already begun to rise before the Plan commenced, and the upward trend continued until August 1957, the price index for that month being 112 as compared to 89 in May 1955, 98 in March 1956 and 108 in December 1956. Undoubtedly, the level of prices in the first half of 1955 was unduly low. Nevertheless. it is evident that the rise in prices of some 14 per cent between April 1956 and August 1957 was indicative of the growing inflationary pressures within the system. The balance of payments situation also took a sharply adverse turn about April 1956, the current account deficit over the eighteen months from April 1956 to September 1957 aggregating to a total of Rs. 591 crores.
Government of India Planning Commission
Government of India Planning Commission
Keywords: Economic Development and Planning